Humidity sensor based on microfiber resonator with reduced graphene oxide - Ahmad, H.; Rahman, M.T.; Sakeh, S.N.A.; Razak, M.Z.A.; Zulkifli, Mohd Zamani (Elsevier, 2016)
A simple relative humidity (RH) sensor based on a tapered single mode fiber loop resonator (MLR) is proposed and experimentally verified. The refractive index of the microfiber in the MLR was modified by environmental humidity, and its emission wavelength changed with RH level. Reduced graphene oxide (rGO) material was used for this device due to its inherent characteristics of high water permeability and high sensitivity whereby long response and recovery times are reduced. Moreover, humidity sensors have been widely used in different fields and are used in the solutions of numerous problems. The performance of tapered fiber was measured with and without rGO and at fiber diameter of 4.04 m. The spectrum was observed to shift with the wavelength as relative humidity increased, and measured sensitivity with rGO was 0.0537 nm/%RH and without rGO was 0.0316 nm/%RH in the range of 30 to 50% relative humidity